Identifying Risk Factors and Improving Preventive Strategies for Febrile Neutropenia in Children with Leukemia Receiving Ciprofloxacin Prophylaxis - Zühre Kaya; Nurettin Alıcı; Serap Kırkız; Ülker Koçak (Turkish Journal of Hematology, 2023)
The purpose of this study was to identify risk factors and improve preventive strategies for febrile neutropenia (FEN) in children with leukemia who were receiving ciprofloxacin prophylaxis. The study included 100 children with leukemia [n=80 with acute lymphoblastic leukemia and n=20 with acute myeloblastic leukemia (AML)]. Patients were divided into two groups based on whether they had three or fewer FEN episodes (Group 1) or more than three FEN episodes (Group 2). Group 1 contained 63 (63%) of the 100 patients, while Group 2 contained 37 (37%). Older age (≥7 years), leukemia type, prolonged neutropenia (>10 days), and the presence of neutropenia and hypogammaglobulinemia at diagnosis were all risk factors for having more than three FEN episodes. Our findings suggest that, in addition to ciprofloxacin prophylaxis, identifying risk factors and improving preventive strategies could help reduce FEN episodes in children with leukemia.